2018
DOI: 10.1177/2381468318765172
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Colorectal Cancer Screening Discussions Between Older Adults and Their Primary Care Providers: A Cross-Sectional Study

Abstract: Introduction. Discussions of colorectal cancer (CRC) screening with older adults should be individualized to maximize appropriate screening. Our aim was to describe CRC screening discussions and explore their associations with patient characteristics and screening intentions. Methods. Cross-sectional survey of 422 primary care patients aged ≥70 years and eligible for CRC screening, including open-ended questions about CRC screening discussions. Primary outcomes were the frequency with which CRC screening discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…48 Another study showed that among older patients who preferred to pursue colorectal cancer screening but were unlikely to benefit, only about one-third changed their minds after discussing screening with their clinicians. 49 Focusing on older patients with recent screening, we found heterogeneity in their willingness to stop screening and that some patients who were reluctant to stop screening may react negatively to recommendation about screening cessation.…”
Section: Discussionmentioning
confidence: 81%
“…48 Another study showed that among older patients who preferred to pursue colorectal cancer screening but were unlikely to benefit, only about one-third changed their minds after discussing screening with their clinicians. 49 Focusing on older patients with recent screening, we found heterogeneity in their willingness to stop screening and that some patients who were reluctant to stop screening may react negatively to recommendation about screening cessation.…”
Section: Discussionmentioning
confidence: 81%
“…Thirteen studies examined breast screening; 14 , 15 , 17 , 18 , 23 , 26 , 29 , 30 , 32 , 39 , 42 – 44 six examined colorectal; 21 , 24 , 25 , 31 , 34 , 40 five examined prostate; 16 , 36 – 38 , 41 one examined cervical; 19 three examined a combination of breast, colorectal, and prostate; 20 , 27 , 33 one examined breast and cervical; 22 and one examined prostate and colorectal. 45 …”
Section: Resultsmentioning
confidence: 99%